2005
DOI: 10.1007/s00427-005-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Myf5 −/− :MyoD −/− amyogenic fetuses reveal the importance of early contraction and static loading by striated muscle in mouse skeletogenesis

Abstract: The mechanical loading of striated muscle is thought to play an important role in shaping bones and joints. Here, we examine skeletogenesis in late embryogenesis (embryonic day 18.5) in Myf5-/-:MyoD-/- fetuses completely lacking striated muscle. The phenotype includes enlarged and fused cervical vertebrae and postural anomalies, some viscerocranial anomalies, long bone truncation and fusion, absent deltoid tuberosity of the humerus, scapular and clavicular hypoplasia, cleft palate, and cleft sternum. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 29 publications
7
102
2
1
Order By: Relevance
“…The effect of mechanical signals during chondrogenesis Studies of paralyzed chick and mouse embryos have revealed that various cartilaginous skeletal elements were shorter and bone eminences were significantly smaller (Hamburger and Waugh, 1940;Hosseini and Hogg, 1991;Rot-Nikcevic et al, 2006;Blitz et al, 2009;Nowlan et al, 2010), and that the size of the proliferative zone (and number of proliferating chondrocytes) in the growth plates of long bones is reduced relative to control embryos (Germiller and Goldstein, 1997;Roddy et al, 2011). Further support for the involvement of mechanical stimulation in chondrocyte proliferation is provided by a study in which cyclic mechanical stimulation of rabbit premaxillae accelerated the rate of chondrocyte proliferation (Wang and Mao, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mechanical signals during chondrogenesis Studies of paralyzed chick and mouse embryos have revealed that various cartilaginous skeletal elements were shorter and bone eminences were significantly smaller (Hamburger and Waugh, 1940;Hosseini and Hogg, 1991;Rot-Nikcevic et al, 2006;Blitz et al, 2009;Nowlan et al, 2010), and that the size of the proliferative zone (and number of proliferating chondrocytes) in the growth plates of long bones is reduced relative to control embryos (Germiller and Goldstein, 1997;Roddy et al, 2011). Further support for the involvement of mechanical stimulation in chondrocyte proliferation is provided by a study in which cyclic mechanical stimulation of rabbit premaxillae accelerated the rate of chondrocyte proliferation (Wang and Mao, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed over the past century have established the contribution of the mechanical load to skeletal development, and specifically to the attachment site (Hall and Herring, 1990;Hamburger, 1939;Hamburger, 1940;Hosseini and Hogg, 1991;Pai, 1965;Rot-Nikcevic et al, 2006;Tremblay et al, 1998). Muscle contraction was demonstrated to regulate bone ridge development, as well as tendon strength and structure (Ralphs et al, 1998;Thomopoulos et al, 2003).…”
Section: Tendon-bone Attachment In Vertebratesmentioning
confidence: 99%
“…Conversely, it has been reported that skeletal muscle can itself model bone development. In Myf5 -/-;Myod -/-double-mutant mice, lacking striated muscle, a number of bone defects have been characterized, including fused vertebrae and long bone truncations (Rot-Nikcevic et al, 2006). This suggests that the forces that muscle exerts on the bone, as well as the forces that bone exerts on muscle are required for normal growth and patterning of both tissues.…”
Section: Temperature and Increased Embryonic Movement Leads Tomentioning
confidence: 99%